Determination Of Dissolution Profile Sprinkle Formulation From Noni Fruit Extract (Morinda Citrifolia L.) - Nurista Dida Ayuningtyas; Yohana Inge Sugiarto; Anita Monalisa (Media Farmasi Indonesia, 2026)
Background: Noni fruit (Morinda citrifolia L.) has immunomodulatory properties due to the presence of scopolamine and quercetin compounds. This immunomodulator activity will be utilized in pharmaceutical products formulated into fine granules (sprinkle formulation). Objective: In this study, dissolution testing of the formulation will be conducted using a type 2 (paddle) apparatus and a medium with a pH value of 1.2 and 4.5. Method: The sprinkle formulation was prepared with the following composition: 16.67% extract, 2.70% Povidone, 2.29% SSG, 20% Mannitol, 3% Aspartame, 0.5% Mg.Stearate, and 54.84% Lactose. The formulation was then subjected to physical granule quality testing and dissolution testing. In the dissolution test, the levels of samples taken during the dissolution test were determined using UV-Vis spectrophotometry. Results: The results obtained were the dissolution profile of quercetin compounds in the sprinkle formulation of noni fruit extract (Morinda citrifolia L) at minute 60 in a pH 1.2 medium was 57.50% ± 1.33 and in a pH 4.5 medium was 86.24% ± 0.69. Statistical analysis of the total flavonoid content (mgQE/gram) in the extract, sprinkle formulation, and the amount of dissolved drug at minute 60 in pH 1.2 and pH 4.5 medium yielded a p-value < 0.05, indicating a significant difference in total flavonoid content among the samples. Conclusion: Sprinkle formulation of noni fruit extract provides significantly different dissolution profiles at pH 1.2 and pH 4.5.